Concentration and Soaking Duration Organic Growth Regulators for Stimulated Jati Unggul Nusantara (JUN) Shoots Cuttings - Wilhelmina Seran; Astin Elise Mau; Mamie Elsyana Pellondo’u (Sangia Publishing, 2020)
Jati Unggul Nusantara (JUN) is a new teak seedling product that is a teak variety obtained from the selection of superior teak clones from all over Indonesia using DNA selection. Vegetative effort propagation performed of JUN with shoot cuttings. Concentration and soaking duration growth regulators are important aspects in vegetative plant propagation especially by shoot cutting. The research was conducted at Maulafa – Kota Kupang from Mei to August 2020, The experiment was arranged in Complete Randomize Design 2 factorial applications with 3 replication. Factors studied are growth regulator concentration of cow urine 50% (A1), cow urine 100% (A2), green bean extract 50% (A3), green bean extract 100% (A4), shallot extract 50% (A5) and shallot extract 100% (A6) while soaking duration consists of 4 factors, 2 hours (B1), 4 hours (B2), 6 hours (B3) and 8 hours (B4). The measured observation parameters are the percentage of life, the period of appearance of shoots, the number of leaves, shoot lenght,, shoot roots and the number of roots. The experiment result showed that variation of concentration organic growth regulator significant effect of JUN shoot cuttings. The treatment of Shallot extract 50% (A5) which affects the percentage of life parameters, the period of appearance of shoots, the number of leaves and shoot lenght. The treatment of shallot extract 100% (A6) which affects the observation parameters of root length and the number of roots. Interaction among the treatment combination of organic growth regulators A6B2 (ZPT 100%) shallot extract and 4 hours soaking duration significant effect on the number of roots.